Cometary dust analogues for physics experiments. Issue 3 (25th June 2022) - Lethuillier, A; Feller, C; Kaufmann, E; Becerra, P; Hänni, N; Diethelm, R; Kreuzig, C; Gundlach, B; Blum, J; Pommerol, A; Kargl, G; Laddha, S; et al.
ABSTRACT: The CoPhyLab (Cometary Physics Laboratory) project is designed to study the physics of comets through a series of earth-based experiments. For these experiments, a dust analogue was created with physical properties comparable to those of the non-volatile dust found on comets. This 'CoPhyLab dust' is planned to be mixed with water and CO2 ice and placed under cometary conditions in vacuum chambers to study the physical processes taking place on the nuclei of comets. In order to develop this dust analogue, we mixed two components representative for the non-volatile materials present in cometary nuclei. We chose silica dust as a representative for the mineral phase and charcoal for the organic phase, which also acts as a darkening agent. In this paper, we provide an overview of known cometary analogues before presenting measurements of eight physical properties of different mixtures of the two materials and a comparison of these measurements with known cometary values. The physical properties of interest are particle size, density, gas permeability, spectrophotometry, and mechanical, thermal, and electrical properties. We found that the analogue dust that matches the highest number of physical properties of cometary materials consists of a mixture of either 60 per cent/40 per cent or 70 per cent/30 per cent of silica dust/charcoal by mass. These best-fit dust analogue will be used in future CoPhyLab experiments.